PERSEPSI KONSUMEN TERHADAP HARGA DAN KUALITAS PANGAN DI PASAR RAKYAT GIANYAR - Ni Gst Ag. Gde Eka Martiningsih; Ida Ayu Made Dwi Susanti; Vandrianus Fernandes, (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2024)
Perception in a general sense is a person's view of something that will make a response to how and with what a person will act. A person's perception of food is what thoughts underlie a person to be used later in choosing and using or consuming what type of food the consumer wants. The purpose of this study was to determine consumer perceptions of food prices at the Gianyar People's Market and to determine consumer perceptions of food quality at the Gianyar People's Market. This research was conducted at the Gianyar People's Market, Gianyar Kelurahan, Gianyar District, Gianyar Regency. The time for carrying out this research activity is to be carried out from April to May 2024. Determination of the sample in this study using the incidental sampling method with the number of respondents. Consumer perceptions were analyzed using a likert scale apporach with three categories. The result showend that consumer perceptions of food prices in the gianyar people’s market werein the good category. Consumer perceptions of food quality were in the good category. Categorize it very well. It is recommended that the seller mintains the quality of the food at competitive prices